Angular-momentum-dependent optical gain spectrum based on stimulated degenerate four-wave mixing. (23rd August 2019) - Zhou, Hai-Tao; Li, Rui-Feng; Dai, Yu-Peng; Wang, Dan; Wu, Jin-Ze; Zhang, Jun-Xiang
Abstract: We experimentally investigate the gain spectrum for a pair of conjugated beams through stimulated degenerate four-wave mixing (DFWM) using Cs vapor. The experimental results showed that the DFWM can only occur when the angular momentum of the ground state is larger than or equal to that of the excited state ( F g  ≥  F e ) for the F g  →  F e transition. It was considered that, in all Zeeman sublevels, qualitative theoretical analysis shows that the stable ground-state Zeeman coherence and significant atom population on initial pumped sublevels for an N-type transition loop are necessary for DFWM. The highest gain occurred in the case of F g  =  F e . Finally, the gain against various experimental parameters is also studied, and a pair of frequency-degenerate conjugated beams with gain over 10 is obtained in a wide range of pump detuning.